THE DESIGN OF THE RAHWANA CHARACTER AS AN ADAPTATION OF THE RAMAYANA RELIEFS ON THE PRAMBANAN TEMPLE INTO ANIMATION - alfan, alfan setyawan; Nisa, Nisa Fijriani (ISI Press Institut Seni Indonesia Surakarta, 2025)
The Ramayana reliefs on the walls of the Shiva and Brahma temples within the Prambanan temple complex serve as a visual narrative that depicts Rama's journey to rescue Dewi Sinta from Rahwana. The visual appearance of the relief represents an acculturation of Indian and Javanese cultures. The narrative imparts lessons on the concept of morality through the portrayal of people representing both good and evil. This article intends to conceptualize the character of Rahwana from the perspective of the Ramayana reliefs as an animated character design. This design employs the Visual Language (Bahasa Rupa) and Adaptation (Alihwahana) approaches through data collecting, translation, and work compilation phases. This design's outcome is the Rahwana design, featuring body decoration, color, and the configuration of the Dasamuka and a T-Pose. This character design offers the possibility for further development to meet the requirements of animated film production with Indonesian characteristics